Trends in time-to-pregnancy in the USA: 2002 to 2017. Issue 8 (21st May 2021) - Eisenberg, Michael L; Thoma, Marie E; Li, Shufeng; McLain, Alexander C
Abstract: STUDY QUESTION: Has there been there a temporal change in time-to-pregnancy (TTP) in the USA. SUMMARY ANSWER: Overall, TTP was stable over time, but a longer TTP for women over 30 and parous women was identified. WHAT IS KNOWN ALREADY: Fertility rates in the USA have declined over the past several years. Although these trends have been attributed to changing reproductive intentions, it is unclear whether declining fecundity (the biologic ability to reproduce measured by TTP in the current report) may also play a role. Indeed, trends based on declining sperm quality and higher utilisation of infertility treatment suggest fecundity may be falling. STUDY DESIGN, SIZE, DURATION: This cross-sectional survey data from the National Survey of Family Growth was administered from 2002 to 2017. The surveys are based on nationally representative samples of reproductive-aged women in the USA. Interviews were conducted in person or through computer-assisted self-administration of sensitive questions. PARTICIPANTS/MATERIALS, SETTING, METHODS: The study included women who self-reported time spent trying to become pregnant allowing utilisation of the current duration approach to estimate the total duration of pregnancy attempt (i.e. TTP). In all, 1202 participants were analysed over each study period. To estimate a TTP distribution overall and by parity, we used a piecewise constant proportional hazards model that accounts for digit preference. Accelerated-failure-time regression models, which were weighted to account for the sampling design, were used to estimate time ratios (TRs). Models were adjusted for age, BMI, race, education, relationship status, parity, pelvic inflammatory disease treatment and any reproductive problems. MAIN RESULTS AND THE ROLE OF CHANCE: Of the participants analysed, the average age was 31.8 and BMI was 28.6, which was similar across the survey periods. Relationship status was the only demographic characteristic that changed over time. All other variables remained constant across the study periods. Overall, TRs comparing TTP between 2002 and 2017 increased slightly (TR: 1.02, 95% CI: 0.99, 1.04). When stratified by parity, parous women had a longer TTP over the later years of the study (TR: 1.04, 95% CI: 1.01, 1.06). TTP remained constant for nulliparous women. Similarly, TTP also increased over time for women over age thirty (TR: 1.02, 1.00, 1.05) but not for women under age thirty. LIMITATIONS, REASONS FOR CAUTION: Small changes in data collection over time may have impacted the findings. We accounted for this in sensitivity analyses using imputed data. Overall, TRs were slightly attenuated using the imputed data, but represented similar patterns to the original data. Results for parous women and women over 30 remained consistent in the sensitivity analyses. WIDER IMPLICATIONS OF THE FINDINGS: Consistent with reports of falling fertility rates and sperm counts, this study suggests parous and older couples in the USA may be taking longer to become pregnant. Although trends were suggestive of a small overall increase in TTP, particularly for parous women and women over age thirty, additional data are needed to attempt to understand these trends given the societal, economic and public health implications related to fecundity. STUDY FUNDING/COMPETING INTEREST(S): Funding was provided by National Institutes of Health grant R03HD097287 to A.C.M. There are no competing interests. TRIAL REGISTRATION NUMBER: N/A.